Adaptation of Digital Technology in Radio Stations in Indonesia) - Harliantara (Indonesian Journal of Business Analytics, 2024)
Digital technology has had a significant impact on radio stations in Indonesia. This makes radio more accessible and allows community involvement to listen to radio broadcasts online. In addition, digital technology speeds up the broadcast process and allows the use of simulcast. This research was conducted qualitatively, using observation and literature study to collect and process data from reliable sources. Research has found that radio stations use digital technology to promote their programs and communicate with their listeners. They also use social networks to learn about public issues and increase public engagement.